2018
DOI: 10.1093/trstmh/try138
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication with non-prescribed pharmaceutical agents in an area of low malaria transmission in northern Tanzania: a community-based survey

Abstract: BackgroundSelf-treatment with antimicrobials is common in sub-Saharan Africa. Little is known about the prevalence of this practice where malaria transmission intensity is low, and little is known about the prevalence of self-treatment with other medications such as antihypertensives and antihyperglycemics.MethodsA two-stage randomized population-based cluster survey with selection proportional to population size was performed in northern Tanzania. Self-identified healthcare decision-makers from randomly selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…In a similar study conducted in Nigeria, it was observed that 76.6% of caregivers practice home‐based treatment of malaria for their children with a majority (99%) adopting inappropriate use of drugs for the treatment of malaria 30 . This is because most ACTs are available as over‐the‐counter drugs in most patent and propriety medicine vendor stores (PPMVs) where close to 60% of patients access self‐treatment for febrile conditions including malaria 31‐36 . Reasons adduced for this include the high cost of treating malaria and the low‐income level of postpartum mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study conducted in Nigeria, it was observed that 76.6% of caregivers practice home‐based treatment of malaria for their children with a majority (99%) adopting inappropriate use of drugs for the treatment of malaria 30 . This is because most ACTs are available as over‐the‐counter drugs in most patent and propriety medicine vendor stores (PPMVs) where close to 60% of patients access self‐treatment for febrile conditions including malaria 31‐36 . Reasons adduced for this include the high cost of treating malaria and the low‐income level of postpartum mothers.…”
Section: Discussionmentioning
confidence: 99%
“…This accrues to an average cost of approximately 11 USD based on a conversion rate of N360 per USD which corroborates the fact that the high cost of treating malaria in the clinic/health centers may have encouraged postpartum mothers to self‐medicate. Therefore, the provision of free antimalarial drugs by the government and a reduction in the cost of treatment in clinics and hospitals will enhance appropriate malaria treatment practices 35‐37 …”
Section: Discussionmentioning
confidence: 99%
“…This result is in sharp contrast to a study in Northern Tanzania where the prevalence of self-medication with antihypertensives and anti-diabetic drugs was 0.6%. 17 Such ignorance may result in poor attendance at hypertensive and diabetic follow-up clinics, missed appointments, and poor outcomes of treatment. These misconceptions should be addressed through individualized health education and counseling session during screening clinics, well-person's clinics, and medical specialty clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Residents living in the research districts report affiliation with Christianity (81%) and Islam (16%). 15 Islam appeared in coastal East Africa centuries before Christianity, with the expansion of trade in the 19th century spreading Islam to the interior of Tanzania. [16][17][18] Christianity was introduced in the Kilimanjaro Region by German and British missionaries in the 19th century.…”
Section: Methodsmentioning
confidence: 99%